1997
DOI: 10.1021/ic960657e
|View full text |Cite
|
Sign up to set email alerts
|

Acid−Base and Electrochemical Properties of the MLCT Excited States and One-Electron-Reduced Forms of Ruthenium(II) Complexes Containing 2-(2‘-Pyridyl)pyrimidine and 2,2‘-Bipyridine in Aqueous Solution

Abstract: The acid-base and electrochemical properties of the MLCT excited states and the one-electron-reduced forms of the three Ru(bpy)(3)(-)()(p)()(pypm)(p)()(2+) complexes, where bpy = 2,2'-bipyridine, pypm = 2-(2'-pyridyl)pyrimidine, and p = 1-3, have been examined in aqueous solution; a determination has been made of the ground- and excited-state electrochemical potentials, the values of the pK(a) and deprotonation rate constants of the conjugate acids of the excited states and the one-electron-reduced complexes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 23 publications
(55 reference statements)
5
34
0
Order By: Relevance
“…+ and [Ru(bpy) 2 (pypmHC À )] 2 + (pypm = 2-(2'-pyridyl)pyrimidine) species produced by PR, [25] the mechanism for the formation of [Ru(bpy) 2 …”
Section: (Pypmc)]mentioning
confidence: 99%
“…+ and [Ru(bpy) 2 (pypmHC À )] 2 + (pypm = 2-(2'-pyridyl)pyrimidine) species produced by PR, [25] the mechanism for the formation of [Ru(bpy) 2 …”
Section: (Pypmc)]mentioning
confidence: 99%
“…Bands in the 700-850 and 1050-1150 nm regions are weak (" $ 10 3 M À1 cm À1 ) and systematically shifted to higher energy on going from ctc to ccc-isomer. In d 6 -metal complexes, multiple charge transitions can arise from low-symmetry splitting of the metal levels, from the mixing of singlet and triplet configurations in excited states via spin-orbit coupling and from the presence of more than one interacting ligand, each contributing one * level [23][24][25][26]. The absorption properties of the present complexes have been compared with the spectra of ruthenium(II) analogues and it is concluded that the bands are blue shifted by 80-100 nm in the osmium(II) complexes along with appearance of a low energy band in the near-IR region.…”
Section: Isomers Of Osmium(ii) Complexes 1277mentioning
confidence: 99%
“…This is in agreement with the -acidity order arylazopyridine > arylazoimidazole > naphthylazoimidazole. The presence of an additional aromatic ring in naphthyl derivatives may increase the electron density in the molecule and is one reason for reduced -acidity [26,27]. 1 H NMR spectra of the complexes were examined to determine isomeric structure.…”
Section: Isomers Of Osmium(ii) Complexes 1277mentioning
confidence: 99%
“…[8,9] Many life processes, such as enzymes, operate within a very narrow pH window, but more work is required to broaden pH windows, and to improve the sensitivity of pH responses. For example, the complex [Ru(η 6 -p-cymene)Cl 2 (pta)] (pta = 1,3,5-triaza-7-phosphatricyclo[3.3.1.1]decane) was reported to exhibit interesting pH-dependent DNA damage and selectivity towards cancer cells.…”
Section: Introductionmentioning
confidence: 99%